2003
DOI: 10.1037/1064-1297.11.1.79
|View full text |Cite
|
Sign up to set email alerts
|

Repeated spatial acquisition: Effects of NMDA antagonists and morphine.

Abstract: Effects of morphine and 2 N-methyl-D-aspartate (NMDA) receptor antagonists, phencyclidine and LY235959, were studied using a within-subject, repeated-acquisition/performance procedure adapted to the Morris Swim Task. In the performance component, subjects swam to a hidden platform that was always in the same location in the pool. In the acquisition component, the platform was moved to a different place for each session. Baseline training produced rapid and direct swims to the platform in the performance compon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
10
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 33 publications
2
10
1
Order By: Relevance
“…Both the selective effects of DZP and the nonselective effects of morphine obtained in the present study with rats are consistent with those previously reported under traditional RAP procedures in primates (Moerschbaecher and Thompson 1983;Moerschbaecher et al 1985;Thompson et al 1987;France et al 1991), but not with those under the RAP/MST with rats (Keith and Galizio 1997;Galizio et al 2003). It should be noted here that Cohn and Cory-Slechta (1993) also reported selective, albeit only slight, effects of DZP under a RAP procedure with response sequences in rats, and Baron and Moerschbaecher (1996) reported that several NMDA antagonists impaired acquisition of behavioral chains in rats (although their conclusions were based on between-group, rather than within-subject, comparisons of learning and performance).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Both the selective effects of DZP and the nonselective effects of morphine obtained in the present study with rats are consistent with those previously reported under traditional RAP procedures in primates (Moerschbaecher and Thompson 1983;Moerschbaecher et al 1985;Thompson et al 1987;France et al 1991), but not with those under the RAP/MST with rats (Keith and Galizio 1997;Galizio et al 2003). It should be noted here that Cohn and Cory-Slechta (1993) also reported selective, albeit only slight, effects of DZP under a RAP procedure with response sequences in rats, and Baron and Moerschbaecher (1996) reported that several NMDA antagonists impaired acquisition of behavioral chains in rats (although their conclusions were based on between-group, rather than within-subject, comparisons of learning and performance).…”
Section: Discussionsupporting
confidence: 94%
“…For example, N-methyl-D-aspartate (NMDA) antagonists such as dizocilpine (DZP) selectively impair acquisition of response sequences in monkeys at doses that do not affect performance (Moerschbaecher et al 1985;Thompson et al 1987;France et al 1991). In contrast, neither competitive (e.g., LY235959) nor noncompetitive (e.g., DZP or phencyclidine) NMDA antagonists selectively impair spatial acquisition in rats under the RAP/ MST (Keith and Galizio 1997;Galizio et al 2003). Conversely, opiate agonists (e.g., morphine) show an opposite profile of effects; that is, they selectively impair spatial acquisition in rats under the RAP/MST , but not acquisition of response sequences in monkeys (Moerschbaecher and Thompson 1983;Moerschbaecher et al 1985).…”
Section: Introductionmentioning
confidence: 95%
“…Another possible explanation of the differences between the present outcomes and those of more traditional RAP studies would emphasize the potential of pharmacological differences between spatial and non-spatial learning tasks. For example, a study from our laboratory found that morphine selectively affected acquisition in a spatial navigation task (Galizio et al, 2003), but morphine and other opiates have generally been associated with non-selective effects in RAP procedures involving response chains or other non-spatial learning tasks (c.f., Galizio et al, 2006). Although the procedures used in the present study do not involve spatial navigation, learning the target location on the two-dimensional screen certainly required spatial discrimination and perhaps can be viewed as presenting different requirements than more traditional RAP tasks.…”
Section: Discussionmentioning
confidence: 99%
“…In support of a non-mnemonic account of the Morris findings, pre-training experience in the MST abolishes the ability of NMDA antagonists to interfere with new spatial learning except at very high doses that also produce motor impairments (Bannerman, Good, Butcher, Ramsay, and Morris, 1995; Saucier and Cain, 1995). Further, in a repeated acquisition task in the MST, learning of a new spatial location is impaired only at relatively high doses of NMDA antagonists that also interfere with the ability to swim to a previously learned location (Galizio, Keith, Mansfield, and Pitts, 2003; Keith and Galizio, 1997). However, Steele and Morris (1999) observed NMDA antagonist impairments using a procedure in which rats learned to swim to a new platform location each session, but only when the delay between the first and second trials was relatively long (20 minutes and 2 hours); no impairment was observed at shorter delays (15 seconds) comparable to those used in the other repeated acquisition studies.…”
Section: 0 Introductionmentioning
confidence: 99%